Village Midline Study: Karnal, Haryana State, India - Prasad, Sanjay; Kargwal, Kanchan; Sharma, Namrata; Jagannath, Pratyaya; Nagpal, Mansi; Khatri-Chhetri, Arun (2020)
This report summarizes the findings of the Pakhana village midline study (VMS), one of the CCAFS benchmark site in Karnal district, India. The study was conducted from June 14th to 17th 2019 to complement an earlier household midline survey and village baseline survey which were conducted in the same district. The village midline study aims to document changes reported since the village baseline study on some fundamental indicators of natural resource use, the organizational landscape, weather and agriculture-related information networks, as well as information on mitigation options. The study used participatory methods of data collection in which men and women participants were split to form two non-mixed groups. The two groups reflected on changes in the state of resources that were identified at the time of the baseline study. During the midline study, men and women participants identified ten organizations supporting the community in agriculture, livestock, Micro Finance Institution (MFI), education, food distribution, and community development. The main focus of the food security-related organizations identified was on food availability and to a lesser extent on food access and utilization. NRM related organizations were all affiliated with the government and had limited engagement with climate change-related issues and remained focused on agriculture or livestock. All identified organizations were categorized as weak and suffering from a lack of funding and human resources. Furthermore, the groups identified several sources of information on agricultural production, markets, weather, health and nutrition, livestock, and climate change. The population uses existing home appliances such as phones, mobiles, electricity, television and radio to access information. Farming related information was the most sought after for the men’s group, followed by climate change, weather and market prices. Women reported seeking all types of information equally. The most popular sources of information were friends, relatives, neighbours, radio and television. Other options such as accessing market prices information via mobile phones were identified but used less frequently. Internet is becoming widely popular and a reliable source of information among the villagers. Finally, the recommendations from the community are focused on improving soil fertility, water availability, groundwater quality, farm profitability, expansion opportunities, and climate change mitigation interventions. With improved access to assistance and capacity building that meet local needs, Pakhana is well-positioned to adequately address its evolving conditions.